Investigation of the Localisation of FtsZ in Pathogenic E. coli Upon Bacteriophage Addition in a Human Cell Model as a Biomarker for Antibacterial Agents. Issue 5 (27th May 2022) - Dhanoa, Gurneet; Roper, David; Sagona, Antonia
Abstract : Antimicrobial resistance is a growing problem worldwide and has created a need for novel antibacterial agents and strategies. Escherichia coli is one of the most common Gram-negative pathogens and is responsible for infection leading to neonatal meningitis and sepsis. The FtsZ protein is a bacterial tubulin homolog required for cell division in most species, including E. coli. Agents that block cell division have been shown to mis-localise FtsZ, including the bacteriophage λ encoded Kil peptide, resulting in defective cell division and a filamentous phenotype, and therefore FtsZ may be an attractive target for new antimicrobials. In this project, we are interested in studying the localisation of FtsZ in pathogenic E. coli in the presence and absence of human cell cultures, in order to establish how and if this localisation changes upon infection. We are also interested in whether bacteriophages specifically attacking pathogenic E. coli have an effect on the localisation of FtsZ in a human cell environment and want to study the mechanism of this process. We have observed E. coliFtsZ localising to the cell midbody as a ring in both a K12 strain and in the K1 strain EV36 using confocal microscopy. These strains were used to infect human cerebral microvascular endothelial cells (hCMEC/D3) to create a meningitis model. We will present our results showing the effect of the Kil peptide and bacteriophages on this localisation within the model system, in an effort to validate FtsZ as a potential biomarker for antibacterial agents.